2014
DOI: 10.1016/j.virol.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Capsid protein: Evidences about the partial protective role of neutralizing antibody-independent immunity against dengue in monkeys

Abstract: The role of cellular immune response in dengue virus infection is not yet fully understood. Only few studies in murine models propose that CD8(+) T-cells are associated with protection from infection and disease. At the light of recent reports about the protective role of CD8(+) T-cells in humans and the no correlation between neutralizing antibodies and protection observed in several studies, a vaccine based on cell-mediated immunity constitute an attractive approach. Our group has developed a capsid-based va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…While NS3 and NS5 antigens are dominant for both CD4 + and CD8 + T-cell responses, C and NS2A are dominant for CD4 + but not CD8 + T-cell responses [8]. The immunodominance of the capsid is of particular interest in the light of recent studies showing that a capsid-based vaccine from DENV-2 was able to induce protective T-cell-mediated immunity in monkeys, without the contribution of neutralizing antibodies, and the fact that the DENV-derived C is not present in a chimeric dengue vaccine (CYD) [26,27]. Different HLA class II molecules were associated with responses of different breadth and magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…While NS3 and NS5 antigens are dominant for both CD4 + and CD8 + T-cell responses, C and NS2A are dominant for CD4 + but not CD8 + T-cell responses [8]. The immunodominance of the capsid is of particular interest in the light of recent studies showing that a capsid-based vaccine from DENV-2 was able to induce protective T-cell-mediated immunity in monkeys, without the contribution of neutralizing antibodies, and the fact that the DENV-derived C is not present in a chimeric dengue vaccine (CYD) [26,27]. Different HLA class II molecules were associated with responses of different breadth and magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…In this perspective, a recent dengue challenge study in immunized rhesus macaques revealed an alternative platform of assessing vaccine immunogenicity and efficacy by CMI protection coupled to viremia reduction (Gil et al, 2014). Although the extrapolation of vaccine efficacy from NHPs to clinical benefit is still unclear due to possible discrepancies in serotype interference of immunogenicity between macaques and humans (Guy et al, 2009), the assessment of both humoral and CMI induction in immunized NHPs makes it attractive for examining vaccine effectiveness.…”
Section: A Nonhuman Primatesmentioning
confidence: 99%
“…Previous studies showed that the T cell response generated after immunization with the C protein protected Balb/c mice from challenge with the homologous serotype [17]. The partial protective capacity of this molecule in monkeys was also described recently [18]. To combine B cell-and T cell epitopes in a single recombinant DENV construct, a fusion protein of the dengue virus E domain III (DIII) and the capsid (C) protein (DIIIC) has been developed as a potential vaccine candidate.…”
Section: Introductionmentioning
confidence: 67%